DAMPAK EL NIÑO DAN LA NIÑA TERHADAP SUHU MAKSIMUM DI KABUPATEN TEMANGGUNG - Firmansyah, Anugrah Jorgi; Nurjani, Emilya; Sekaranom, Andung Bayu (J SIG (Jurnal Sains Informasi Geografi), 2025)
This study analyzes the impact of the El Niño and La Niña phenomena on the maximum temperature in Temanggung Regency in the period 1995 to 2024. The El Niño and La Niña phenomena can affect temperature and rainfall which have the potential to change local climate conditions and cause hydrometeorological disasters. The method used in this study is spatial analysis using Google Earth Engine, ArcGIS, RStudio software, as well as monitoring the Oceanic Niño Index (ONI) to identify the El Niño and La Niña phases. The maximum temperature data obtained from the ERA5 reanalysis was corrected with AWS observation data. The mean ratio bias correction method is quite effective in improving the average correlation value of the ERA5 dataset in Temanggung Regency against AWS observation data. The previous average correlation value of -0.1 (before bias correction) strengthened to 0.685 (after bias correction). The data correction factor for ERA5 was 1.3204, which was applied to all ERA5 data points and can improve the MBE, RMSE, MAE, and PBIAS values to be smaller approaching zero so that the maximum temperature data from ERA5 can be used for data processing in this region. The results of the study indicate that the El Niño phase causes an increase in maximum temperature, while the La Niña phase tends to decrease the maximum temperature. Significant maximum temperature anomalies were recorded during the El Niño phase, with the highest temperature reaching 41°C in October or increasing by around 7.89% compared to the neutral phase, which can increase the potential risk of drought. During the La Niña phase, the average largest decrease in temperature was in November at -1.53°C or around 4.14% compared to the neutral phase. This study provides important insights for climate change mitigation planning in the Temanggung area, especially in the agriculture and health sectors.